Evolutionary algorithms for active vibration control of flexible manipulator [electronic resource] - Hanim Mohd. Yatim, 1988-, author 546463; Intan Zaurah Mat Darus, supervisor 559143; Maziah Mohamad, supervisor 392309; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Doktor Falsafah (Mekanikal))